2020
DOI: 10.1182/bloodadvances.2020002474
|View full text |Cite
|
Sign up to set email alerts
|

Blastic plasmacytoid dendritic cell neoplasms: results of an international survey on 398 adult patients

Abstract: The purpose of this study is to describe the clinical and prognostic features and to evaluate the outcome of different therapeutic approaches among patients with blastic plasmacytoid dendritic cell neoplasm (BPDCN) who have been diagnosed and treated in different institutions. A total of 398 patients from 75 centers were included in the study. Treatment consisted of non-Hodgkin lymphoma (NHL)–like regimens in 129 (32.8%) patients and acute leukemia (AL)–like regimens in 113 (23.5%) patients. In 61 (15.5%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 49 publications
1
71
0
1
Order By: Relevance
“…Progress in this field is impacted by the use of accurate methods for detecting CD123 expression in candidate malignancies. Unlike in BPDCN, where CD123 is overexpressed uniformly in malignant pDCs [64,86], its expression in other malignancies is limited to certain cell types and sometimes the microenvironment, pre-inflammatory, and inflammatory contexts [124]. Advances in detection techniques, such as FC, CyTOF, and CODEX V R , might overcome these limitations, thus allowing the individualization of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in this field is impacted by the use of accurate methods for detecting CD123 expression in candidate malignancies. Unlike in BPDCN, where CD123 is overexpressed uniformly in malignant pDCs [64,86], its expression in other malignancies is limited to certain cell types and sometimes the microenvironment, pre-inflammatory, and inflammatory contexts [124]. Advances in detection techniques, such as FC, CyTOF, and CODEX V R , might overcome these limitations, thus allowing the individualization of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, tagraxofusp is the only FDA-approved CD123-targeted therapy; it is approved for the treatment of newly diagnosed and relapsed/refractory (R/R) BPDCN in adult and pediatric patients [19]. MB-102 T cells are genetically modified to express a costimulatory CD123-specific chimeric antigen receptor (CAR) and a truncated epidermal growth factor receptor (CD123CAR-CD28-CD3f-EGFRt) that were granted Orphan Drug Designation in 2018 for the treatment of BPDCN and in 2019 for AML [86]. Table 2 depicts some of the anti-CD123 therapies that are being tested for the treatment of CD123þ hematologic malignancies.…”
Section: Cd123-targeted Therapiesmentioning
confidence: 99%
“…Other dendritic cell markers not tested in this case are CD68, CD123 and BDCA-2/CD303 [14] . This patient also showed positivity for terminal deoxynucleotidyl transferase (TdT), which is associated to a better prognosis [8] .…”
Section: Case Reportmentioning
confidence: 90%
“…Current literature, based on case reports in children supports the use of acute leukemia treatment regimens as the most beneficial option [7] . While, recently, a larger cohort in adults has reported the best outcomes for AL-like regimen followed by allogenic hematopoietic stem cell transplantation [8] . Although there is no standardized treatment for BPDCN, one study reported that adults treated with AML-like, ALL-like and high-dose methotrexate with asparaginase (Aspa-MTX) chemotherapies showed increased survival and remission compared to other treatments such as CHOP-like (classical regimen used in the treatment of non-Hodgkin lymphomas and combining cyclophosphamide, doxorubicin, vincristine, and prednisone) and not otherwise specified (NOS) regimens (all other drugs alone or in combination) [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Children also were less likely than adult patients (27% vs. 57%, P<0.01) to relapse after complete remission. We also listed the response rates and survival outcomes with different regimens of the main BPDCN patients reported in literature [8,73,75,86,[91][92][93][94][95] (table 2).…”
Section: Clinical Course and Treatment Of Bpdcnmentioning
confidence: 99%